Analisis Penyelesaian Sengketa Konsumen Terhadap Perkara Pencantuman Klausula Baku Pada Karcis Parkir Berdasarkan Putusan Nomor: 001/BPSK-LLG/Arbitrase/I/2022 diBadan Penyelesaian Sengketa Konsumen Kota Lubuklinggau - Novan; Agustinus Samosir; Fitriyani (Jurnal Riset Multidisiplin Edukasi, 2025)
This journal discusses the Consumer Dispute Resolution Process regarding the Case of Including Standard Clauses on Parking Tickets at the Lubuklinggau City Consumer Dispute Resolution Agency. The consumer dispute resolution process provides knowledge about disputes between consumers and business actors, so that all their rights can be recognized and protected. The main problem is what is the process for resolving consumer disputes at the Lubuklingau City Consumer Dispute Resolution Agency. The sub-problems are: How is the analysis of consumer dispute resolution regarding the case of including standard clauses on parking tickets based on decision Number: 001/BPSK-LLG/Arbitrase/l/2022 at the Lubuklinggau City Consumer Dispute Resolution Agency.  What are the considerations of the Tribunal in deciding the case of including standard clauses on parking tickets based on decision Number: 001/BPSK-LLG/Arbitrase/l/2022 at the Lubuklinggau City Consumer Dispute Resolution Agency. This type of research is normative-empirical. Normative-empirical (applied) legal research is research that examines the implementation or implementation of positive legal provisions (legislation) and written documents in action (factual) on each particular legal event that occurs in society. The minimum approach that must be present in normative-empirical legal research is a conceptual approach, a legislative approach, because there is no research that does not start from the concepts and regulations in force, then supplemented with one or more approaches in empirical legal research. Data collection techniques include; collecting secondary data (library and written documents) through library studies and document studies and collecting primary data (data on the object of research carried out) through interviews with respondents and informants as well as resource persons, questionnaires or lists of questions and observations of the research location to be carried out. This research results in the conclusion that the mechanism for resolving consumer disputes using parking services in the event of the loss of motorized vehicles in the parking area can resolve disputes through channels outside of court. Consumers have the right to sue for motorbikes that are lost in the parking area, because Law Number 8 of 1999 concerning Consumer Protection guarantees consumers' right to sue business actors who have committed violations through institutions tasked with resolving disputes between consumers and business actors (in this case the Consumer Dispute Resolution Agency). The settlement process is through (conciliation, mediation, arbitration). The panel's consideration in examining and deciding cases is by examining the petition, evidence, deepening the evidence, listening to witnesses and expert witnesses and testing them legally and considering compensation. Considering the large number of dispute cases, consumers must be careful about their rights and obligations in understanding an agreement with a business actor before agreeing to the agreement.